The importance of reporting to the anxiety and the resilience of patients will undergo a colonoscopy - Olmo-Conesa, Juana María; Gómez-Díaz, Magdalena (Revista Española de Comunicación en Salud, 2019)
Introduction: Colonoscopy is a highly demanded technique due to its benefits, but it is nevertheless an uncomfortable procedure where pain and fear of the unknown can create a certain degree of anxiety. Objectives: The main objective of this study is to evaluate the level of anxiety and resilience in patients going to undergo colonoscopy, and check if the received information and knowledge affects these variables. Methodology: This is an observational, descriptive, transversal and prospective study. The study sample included 100 patients, 50 tested with conscious sedation and 50 with deep sedation, who underwent a colonoscopy. The assessment tools used were: State-Trait Anxiety Inventory (STAI)y Connor-Davidson Resilience Scale (CD-RISC-10). Results: 52% of the sample experienced a high degree of anxiety. This level of anxiety related statistically significantly with receiving information or not (p =. 00) and with the same level, sufficient or insufficient (p =. 00). And patients more resilient turned out to be those that yes knew the test or were briefed on it. Conclusion: We can conclude that more information less anxiety and greater level of resilience against a colonoscopy.
Keywords: anxiety; resilience; colonoscopy; nursing; information; conscious sedation; deep sedatio